Normative Fragmentation in Indonesian Notary Law: Regulatory Harmonization of Cyber Notary and Electronic Signatures toward Structural Justice - Savita, Salsa Rima; Mahfud, Muh. Afif; NGA, Pham Thanh (Potret Pemikiran, 2025)
Indonesia's notary law framework remains normatively fragmented, as the Notary Law (UUJN) requires physical presence while the Electronic Information and Transactions Law (ITE Law) recognizes electronic signatures as legally binding instruments. This contradiction prevents notaries from issuing authentic electronic deeds, creates legal uncertainty, and structurally excludes vulnerable populations including remote communities, migrant workers, and micro-enterprise operators from accessing civil legal services. This study examines the normative legitimacy of electronic signatures within the Indonesian notary system, identifies the structural consequences of regulatory fragmentation on vulnerable populations, and proposes a justice-oriented harmonization framework for inclusive digital notarial services. Employing normative juridical methodology with statutory, conceptual, and comparative approaches, this study analyzes Indonesian legislation alongside regulatory experiences from the Netherlands, Brazil, Rwanda, Singapore, and Turkiye. The findings reveal three critical issues: normative contradiction between the UUJN and the ITE Law regarding remote appearance and authentication standards; the absence of explicit statutory recognition of cyber notary mechanisms; and disproportionate structural barriers to civil legal access for vulnerable populations produced by regulatory ambiguity. Harmonization requires legislative amendment, institutional infrastructure development, and justice-oriented governance design that ensures digital notarization expands rather than reproduces existing structural inequalities in access to legal services.